Engineering Emulsion Gels as Functional Colloids Emphasizing Food Applications: A Review - Abdullah,; Liu, Lang; Javed, Hafiz Umer; Xiao, Jie (Frontiers in Nutrition, 2022)
Gels are functional materials with well-defined structures (three-dimensional networks) assembled from the dispersed colloids, and capable of containing large amount of water, oil, or air (by replacing the liquid within the gel pores), known as hydrogel, oleogel, and aerogel, respectively. An emulsion gel is a gelled matrix filled with emulsion dispersion in which at least one phase, either continuous phase or dispersed phase forms spatial networks leading to the formation of a semisolid texture. Recently, interest in the application of gels as functional colloids has attracted great attention in the food industry due to their tunable morphology and microstructure, promising physicochemical, mechanical and functional properties, and superior stability as well as controlled release features for the encapsulated bioactive compounds. This article covers recent research progress on functional colloids (emulsion gels), including their fabrication, classification (protein-, polysaccharide-, and mixed emulsion gels), properties specifically those related to the gel-body interactions (texture perception, digestion, and absorption), and industrial applications. The emerging applications, including encapsulation and controlled release, texture design and modification, fat replacement, and probiotics delivery are summarized. A summary of future perspectives to promote emulsion gels use as the functional colloids and delivery systems for scouting potential new applications in the food industry is also proposed. Emulsion gels are promising colloids being used to tailor breakdown behavior and sensory perception of food, as well as for the processing, transportation, and targeted release of food additives, functional ingredients, and bioactive substances with flexibility in designing structural and functional parameters.